Senior bank loan officers' expectations for loan demand: A note - Dimitris Anastasiou; Khudoykulov Khurshid Khurramovich; Christos Kallandranis (Cogent Business & Management, 2023)
We employ senior bank loan officers' responses regarding actual and expected loan demand from enterprises linking successive surveys to determine the dominant expectation formation mechanism that best describes European senior bank loan officers' expectations. Our findings suggest that the adaptive expectations mechanism is compatible with senior bank loan officers' expectations for loan demand from enterprises. Our study contributes to the understanding of the formation of loan demand expectations, and hence our findings can be beneficial for monetary policy purposes.
Keywords: C33; C53; D84; 650; adaptive expectations; bank lending survey; loan demand; survey‐ based expectations